Variations in plant forms - Crump, Elsie Emeline (My University, 1895)
Introduction: Whenever we think of the great advancement that has been made recently in the department of science – of the great steps that have been taken forward – of the many ideas once so prevalent that have been declared erroneous and thrust aside to be replaced by new truths – whenever we think of this great work that has been done our minds naturally turn toward the man Darwin who has been the shining light guiding so many minds in the path of truth.
Citation: Crump, Elsie Emeline. Variations in plant forms. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Advancement; Department of Science; Darwin; Plant forms; Theses; Manuscripts (documents)